ECAI 2012 20th European Conference on Artificial Intelligence 27-31 August 2012, Montpellier, France Including Prestigious Applications of Artificial Intelligence (PAIS 2012) System Demonstrations Track Proceedings - Raedt, Luc De (IOS Press, 2014)
This volume, which is also available online from http://booksonline.iospress.nl/, contains the papers that have been presented at ECAI 2012, the Twentieth European Conference on Artificial Intelligence. ECAI was held in the beautiful city of Montpellier (France) from August 27 to August 31, 2012. It is the biennial Conference on Artificial Intelligence (ECAI) organised by the European Coordinating Committee for Artificial Intelligence (ECCAI) and the premier forum for presenting AI results in Europe. ECAI is the place for researchers and practitioners of Artificial Intelligence to gather and to discuss the latest trends and challenges in all subfields of AI as well as to demonstrate innovative applications and uses of advanced AI technology.